IMPLEMENTASI MEDIA SARBANEKA UNTUK MENINGKATKAN SOFT SKILL DAN HARD SKILL MAHASISWA PGMI DALAM MATA KULIAH MICROTEACHING - Siti Nurjanah (El-Ihsan: Journal of Contemporary Islamic Education, 2025)
One of the core courses in the Primary Education Study Program is Micro Teaching, which serves as a platform for students to practice teaching skills directly. However, in practice, Micro Teaching often focuses solely on technical aspects, such as the preparation of lesson plans that rely heavily on the lecture method. This approach is considered less effective in shaping teachers who are creative, collaborative, and reflective qualities that fall under soft skills. This condition highlights the need for a more innovative, interactive, and comprehensive learning approach. The Sarbaneka learning media, designed based on educational games, reflective activities, and group work, emerges as a strategic alternative to address these challenges. This research was conducted at the Shalahuddin Al-Ayyubi Islamic Institute in Jakarta, involving all fifth-semester students who had used the Sarbaneka media in their Micro Teaching practicum course. The research employed both quantitative and qualitative approaches. Quantitative data were obtained through surveys as well as pre-tests and post-tests, while qualitative data were collected through in-depth interviews and observations to strengthen the quantitative findings. The validity and reliability of the instruments were tested to ensure data accuracy. The results of the study indicate that the integration of Sarbaneka media in Micro Teaching not only significantly enhances students’ technical competencies (hard skills) but also promotes the development of character and social skills (soft skills) essential for future PGMI (Islamic Primary School Teacher Education) teachers.